Flow cytometric analysis of equine bronchoalveolar lavage fluid cells in horses with and without severe equine asthma. Issue 1 (January 2022) - Kang, Heng; Bienzle, Dorothee; Lee, Gary Kwok Cheong; Piché, Érica; Viel, Laurent; Odemuyiwa, Solomon Olawole; Beeler-Marfisi, Janet
Severe equine asthma (SEA) is a common, debilitating lower airway inflammatory disorder of older horses. Alveolar macrophages (AMs) survey inhaled particulates from barn sources causing them to switch from an anti-inflammatory to a proinflammatory phenotype, resulting in neutrophil recruitment to the lung. This proinflammatory switch may contribute to the development and prolongation of SEA. Validated antibodies to identify the cells involved in the pathogenesis of SEA are lacking. In this study, monoclonal antibodies against CD90, CD163, and CD206 were tested for reactivity with equine leukocytes by immunocytochemistry and flow cytometry. A multi-color flow cytometric assay was developed to identify leukocytes in equine bronchoalveolar lavage fluid (BALF). Four control and 4 SEA-susceptible horses had BALF collected before and after a 48-hour moldy hay challenge. Antibodies against CD90 uniquely labeled equine neutrophils, and antibodies against CD163 and CD206 identified equine macrophages. Postchallenge AM surface expression of CD163 increased in both groups of horses, but the increase was statistically significant in only the SEA-susceptible group ( P = .02). The surface expression of CD206 on AMs increased significantly in the SEA-susceptible group ( P = .03) but was unchanged in the control group ( P = .5). Increased expression of CD163 and CD206 during exacerbation of SEA suggested an association between AM phenotype and lung inflammation. However, functions of AMs in the pathogenesis of SEA remain to be elucidated.